INTERACTIVE INNOVATIVE TECHNOLOGIES DURING THE TEACHING OF THE COURSE «PROJECT MANAGEMENT IN EDUCATION» - RIDKODUBSKA, Hanna (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
Theoretical and applied features of using the innovative interactive technologies during educational activities in the teaching process the discipline «Project Management in Education» Generalization and systematization researching in the field of innovative technologies allowed to justify the main ways of implementing innovative technologies in teaching the discipline. The purpose of the article is to characterize the main ways of implementing interactive innovative technologies during the study of the discipline «Project Management in Education» Expanding the content of the discipline with theoretical knowledge and practice-oriented tasks for the development and implementation of projects in education will significantly enrich and modernize the content of this discipline. Disclosure of the peculiarities of the implementation of innovative technologies during the study of «Project Management in Education» will improve the quality of their training in modern conditions. During the study of each topic of this discipline, the advantages of its implementation are described. Among the features of the use of innovative technologies at each stage of assimilation are substantiated: rationalization of classroom use, increasing the level of independence of master students in making professional decisions and responsibility for their adoption, increasing cognitive activity and critical thinking, individual approach to each educational process student, reorientation change of role relationships, when the student becomes a seeker of their own competencies, and the teacher forms a conscious attitude to the processing of information sources, develops a conscious motivation for the discipline. Reforming the Ukrainian education system causes changes in the content and orientation of social institutions, further development of the educational system, shifting the benchmarks of training highly professional specialists in external monitoring to meaningful analysis of the quality of these reforms, which determines the formation of general, professional and social competencies.